Battery cell and method for producing the same, electric device

CN122968533APending Publication Date: 2026-10-23CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510472467.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-15
Publication Date
2026-10-23

Smart Images

  • Figure CN122968533A_ABST
    Figure CN122968533A_ABST
Patent Text Reader

Abstract

A battery monomer, a preparation method thereof, and an electric device. The battery monomer comprises: an electrode assembly; an aluminum plastic film used for accommodating the electrode assembly, the aluminum plastic film comprising a heat-sealing layer, a metal layer, and a functional material layer, the heat-sealing layer, the metal layer, and the functional material layer being sequentially arranged in a direction away from the electrode assembly; and wherein the functional material layer comprises a functional material, and the functional material comprises a urea group. The technical solution of the present application can improve the packaging reliability of the battery monomer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, and more specifically, to a battery cell, a method for preparing the same, and an electrical device thereof. Background Technology

[0002] With increasing environmental pollution, the new energy industry is attracting more and more attention. Within the new energy industry, battery technology is a crucial factor in its development.

[0003] Pouch batteries have seen rapid development due to their numerous advantages, including being lightweight, thin, having a long cycle life, good safety performance, high energy density, stable discharge platform, excellent power performance, and being environmentally friendly and pollution-free. Pouch batteries typically use an aluminum-plastic film as their outer casing to encapsulate the electrode components. The reliability of this encapsulation is a crucial factor affecting the performance of pouch batteries. Summary of the Invention

[0004] This application is made in view of the above-mentioned problems, and its purpose is to provide a battery cell with high packaging reliability.

[0005] To achieve the above objectives, this application provides a battery cell, a method for preparing the same, and an electrical device thereof.

[0006] In a first aspect, a battery cell is provided, comprising: an electrode assembly; and an aluminum-plastic film for housing the electrode assembly. The aluminum-plastic film includes a heat-sealing layer, a metal layer, and a functional material layer, wherein the heat-sealing layer, the metal layer, and the functional material layer are sequentially disposed along a direction away from the electrode assembly; wherein the functional material layer includes a functional material, and the functional material includes a urea group.

[0007] In this embodiment, the outermost layer of the aluminum-plastic film away from the electrode assembly is a functional material layer. That is, the functional material layer is located on the outermost side of the aluminum-plastic film shell of the battery cell, and the impact of the external environment on the aluminum-plastic film shell is mainly borne by the functional material layer. Therefore, the functional material layer includes a functional material containing urea groups. First, the nitrogen and oxygen atoms in the urea group have strong electronegativity, enabling them to form hydrogen bonds with other molecules or groups, enhancing intermolecular forces and giving the functional material high stability and mechanical strength. Simultaneously, the numerous hydrogen bonds between molecules increase both elasticity and intermolecular sliding stress, increasing frictional energy loss and improving the material's wear resistance. Second, molecules containing urea groups typically have a relatively regular structure, allowing for close packing within the material. This close packing increases intermolecular van der Waals forces, further enhancing the stability of the urea group and the overall strength of the material. Third, the carbonyl group in the urea group resonates with the lone pair electrons on the nitrogen atom, resulting in a more uniform electron cloud distribution and lower molecular energy, thus making the urea group more stable and improving the stability of the functional material. Furthermore, the C-N and C=O bonds in the urea group have relatively high bond energies, requiring significant energy to break, which contributes to the urea group's good stability and resistance to hydrolysis or other chemical reactions, resulting in excellent stability of the functional material. These properties give the functional material excellent impact resistance, elasticity, and abrasion resistance. Therefore, when the functional material layer is impacted by external forces (such as dents in the aluminum-plastic film), the risk of damage or even breakage of the aluminum-plastic film under such impacts can be effectively reduced. Furthermore, during the use of the battery cell, the risk of friction-induced damage to the aluminum-plastic film can be reduced, thereby improving the encapsulation reliability of the battery cell and reducing the risk of leakage.

[0008] In one possible implementation, the functional material further includes a cyclic structure connected to the urea group, the cyclic structure comprising a carbon ring composed of three or more carbon atoms.

[0009] In ring structures, atoms are arranged more tightly, with carbon atoms within the ring linked together by covalent bonds to form a closed ring system that is less prone to deformation and breakage. This geometry helps reduce bond strain and minimize energy loss due to changes in bond length. Therefore, ring structures exhibit higher rigidity, thereby improving the stability, strength, hardness, and modulus of functional materials.

[0010] In one possible implementation, the functional material includes at least one of polyurea material and polyurethane material containing urea groups.

[0011] Polyurea materials use urea groups as repeating units, and contain a large number of urea groups, which can greatly improve the extensibility, flexibility and elasticity of functional materials.

[0012] In one possible implementation, the impact strength K of the aluminum-plastic film satisfies: 60 J / m 2 ≤K≤150J / m 2 .

[0013] In this embodiment, the impact strength of the aluminum-plastic film is within the above-mentioned range, which has good impact resistance and can effectively reduce the risk of damage or even breakage of the aluminum-plastic film under external impact, thereby improving the packaging reliability of the battery cell and reducing the risk of leakage of the battery cell.

[0014] In one possible implementation, the thickness D of the functional material layer satisfies: 5μm≤D≤30μm.

[0015] In this embodiment, the thickness of the functional material layer is set within the above-mentioned range. On the one hand, this ensures that the thickness of the functional material layer is sufficient to provide effective impact resistance. On the other hand, it avoids the functional material layer being too thick and affecting the energy density of the battery cell. Therefore, the thickness setting of the functional material layer in this application can both ensure that the aluminum-plastic film has good impact resistance and improve the energy density of the battery cell.

[0016] In one possible implementation, the bond strength σ between the functional material layer and the metal layer satisfies: 40N / 10cm≤σ≤100N / 10cm.

[0017] In this embodiment, the bonding strength between the functional material layer and the metal layer is within the above-mentioned range, and the two have good adhesion. Therefore, there is no need to set an additional adhesive layer to bond the functional material layer and the metal layer, which can simplify the preparation process, save production costs, and reduce the overall thickness of the aluminum-plastic film, which is beneficial to improving the energy density of the battery cell.

[0018] In a second aspect, a method for preparing a battery cell is provided, comprising: preparing an aluminum-plastic film; and accommodating an electrode assembly in the aluminum-plastic film to prepare the battery cell; wherein preparing the aluminum-plastic film includes: providing a metal layer; preparing a heat-sealing layer on one side surface of the metal layer; and preparing a functional material layer on the other side surface of the metal layer; wherein, when the electrode assembly is accommodated in the aluminum-plastic film, the functional material layer is located away from the electrode assembly, and the functional material layer comprises a functional material, the functional material comprising a urea group.

[0019] In the preparation method of this application embodiment, a functional material layer is prepared on the surface of the metal layer. The functional material layer contains urea groups, which can simultaneously improve the stability, strength, elasticity, and wear resistance of the functional material, giving it good impact resistance, elasticity, and friction resistance. Therefore, when the functional material layer is impacted by external force (e.g., dents in the aluminum-plastic film), the risk of damage or even breakage of the aluminum-plastic film under external impact can be effectively reduced. Furthermore, during the use of the battery cell, the risk of friction-induced damage to the aluminum-plastic film can be reduced, thereby improving the encapsulation reliability of the battery cell and reducing the risk of leakage.

[0020] In one possible implementation, the step of preparing a functional material layer on the other side surface of the metal layer includes:

[0021] The first component and the second component are sprayed onto the other side surface of the metal layer, and the first component and the second component react on the other side surface of the metal layer to generate the functional material.

[0022] In one possible implementation, the first component includes isocyanate monomers, polyols, pigments, and fillers.

[0023] In one possible implementation, the isocyanate monomer includes at least one of toluene diisocyanate (TDI) and its isomers, and diphenylmethane diisocyanate (MDI) and its isomers; the polyol includes at least one of polyether polyol and polyester polyol; the pigment includes at least one of titanium dioxide and iron oxide; and the filler includes at least one of barium sulfate, silica fume, and calcium carbonate.

[0024] In one possible implementation, the second component includes an amino-terminated resin, an amino-terminated chain extender, a leveling agent, and a defoamer.

[0025] In one possible implementation, the amino-terminated resin includes at least one of amino-terminated polyether and amino-terminated polyester; the amino-terminated chain extender includes at least one of ethylenediamine, diethylenetriamine, and m-phenylenediamine; the leveling agent includes at least one of acrylate leveling agents, silicone leveling agents, fluorocarbon leveling agents, polyether-modified leveling agents, and composite leveling agents; and the defoamer includes at least one of silicone defoamers, polyether defoamers, fatty alcohol defoamers, and mineral oil defoamers.

[0026] The aforementioned isocyanate monomers can provide -NCO groups, and the amino-terminated resins can provide -NH2 groups. The isocyanate monomers and amino-terminated resins undergo a curing reaction to form functional materials containing urea groups. Simultaneously, adding polyol raw materials during the above chemical curing process can react with the isocyanate monomers to form prepolymers, adjusting the flexibility, hardness, and other properties of the functional materials. Adding pigments and fillers can further improve the mechanical strength, abrasion resistance, and other properties of the functional materials. Adding amino-terminated chain extenders can synergistically work with the amino-terminated resins to increase the length of the functional material's molecular chains, improving its strength, hardness, and other properties. Adding leveling agents and defoamers can improve the workability and quality of the functional material layers.

[0027] In one possible implementation, the volume ratio of the first component to the second component is 1:10 to 10:1.

[0028] In one possible implementation, the initial curing time t for the reaction of the first component and the second component on the other side surface of the metal layer satisfies: 1 min ≤ t ≤ 60 min.

[0029] In one possible implementation, the initial curing temperature T of the reaction between the first component and the second component on the other side surface of the metal layer satisfies: 5℃≤T≤85℃.

[0030] Setting the reaction conditions (volume ratio, initial curing time, and initial curing temperature) of the first and second components within the above range is beneficial for the two components to react fully, so as to generate a functional material with good impact resistance, elasticity, and wear resistance.

[0031] Thirdly, an electrical device is provided, comprising a battery cell as described in the first aspect and any possible implementation thereof, and / or a battery cell obtained according to the preparation method of the second aspect. Attached Figure Description

[0032] To more clearly illustrate the technical solutions of the embodiments of this application, the drawings used in the embodiments of this application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the drawings without creative effort.

[0033] Figure 1 This is a schematic diagram of the structure of an aluminum-plastic film according to an embodiment of this application;

[0034] Figure 2 This is a schematic structural diagram of a battery cell according to an embodiment of this application;

[0035] Figure 3This is a flowchart of a method for preparing a battery cell according to an embodiment of this application;

[0036] Figure 4 This is a schematic structural diagram of a battery according to an embodiment of this application;

[0037] Figure 5 This is a schematic structural diagram of an electrical device according to an embodiment of this application. Detailed Implementation

[0038] The battery cell and its preparation method, as well as the embodiments of the electrical device, of this application have been described in detail with reference to the accompanying drawings. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid making the following description unnecessarily lengthy and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.

[0039] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0040] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0041] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0042] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0043] Typically, a battery cell includes a positive electrode, a negative electrode, an electrolyte, and a separator. During the charging and discharging process of the battery cell, active ions move back and forth between the positive and negative electrodes, inserting and extracting. The electrolyte acts as a conductor between the positive and negative electrodes. The separator, located between the positive and negative electrodes, primarily prevents short circuits between the positive and negative electrodes while allowing active ions to pass through; for example, the separator can be a membrane. In some embodiments, the above-described battery cell is also referred to as a secondary battery, and the battery cell can be the smallest possible battery unit.

[0044] The development of battery technology must consider multiple design factors simultaneously, such as energy density, cycle life, discharge capacity, charge / discharge rate, and reliability. Pouch batteries have seen rapid development due to their numerous advantages, including being lightweight, thin, having a long cycle life, good safety performance, high energy density, stable discharge platform, excellent power performance, and being environmentally friendly. Unlike hard-shell batteries, pouch batteries typically use thermoplastic film for their packaging, for example, aluminum-plastic film is used to package the electrode components, forming a pouch battery. Before packaging the electrode components with aluminum-plastic film, the film needs to be perforated to create a space that matches the shape of the electrode components, facilitating their fixation within the film. However, the perforation process requires applying impact force to the aluminum-plastic film using a mold, which can cause damage, especially at the corners, leading to battery leakage.

[0045] In some implementations, the probability of aluminum-plastic film damage is reduced by decreasing the depth of the dent. However, reducing the depth of the dent is equivalent to reducing the space for the electrode assembly, thereby limiting the overall thickness of the battery cell and reducing the energy density of the battery cell.

[0046] In view of this, this application provides a battery cell, including an electrode assembly and an aluminum-plastic film for housing the electrode assembly. The aluminum-plastic film includes a heat-sealing layer, a metal layer, and a functional material layer, which are sequentially arranged along the direction away from the electrode assembly. The functional material layer includes a functional material, which includes a urea-based material. In the embodiments of this application, the outermost layer of the aluminum-plastic film away from the electrode assembly is the functional material layer. That is, the functional material layer is located on the outermost side of the aluminum-plastic film shell of the battery cell, and the impact on the aluminum-plastic film shell from the outside is mainly borne by the functional material layer. The functional material layer contains urea groups. First, the nitrogen and oxygen atoms in the urea group have strong electronegativity, enabling them to form hydrogen bonds with other molecules or groups, enhancing intermolecular forces and giving the functional material high stability and mechanical strength. Simultaneously, the numerous hydrogen bonds increase both elasticity and intermolecular sliding stress, increasing frictional energy loss and improving wear resistance. Second, molecules containing urea groups typically have a relatively regular structure, allowing for close packing within the material. This close packing increases van der Waals forces, further enhancing the stability of the urea group and the overall strength of the material. Third, the carbonyl group in the urea group resonates with the lone pair electrons on the nitrogen atom, resulting in a more uniform electron cloud distribution and lower molecular energy, thus stabilizing the urea group and improving the overall stability of the functional material. Furthermore, the C-N and C=O bonds in the urea group have relatively high bond energies, requiring significant energy to break, which contributes to the urea group's good stability and resistance to hydrolysis or other chemical reactions, resulting in excellent stability of the functional material. These properties give the functional material excellent impact resistance, elasticity, and abrasion resistance. Therefore, when the functional material layer is impacted by external forces (such as dents in the aluminum-plastic film), the risk of damage or even breakage of the aluminum-plastic film under such impacts can be effectively reduced. Furthermore, during the use of the battery cell, the risk of friction-induced damage to the aluminum-plastic film can be reduced, thereby improving the encapsulation reliability of the battery cell and reducing the risk of leakage.

[0047] [Battery cell]

[0048] This application provides a battery cell including an electrode assembly and an aluminum-plastic film for housing the electrode assembly.

[0049] Figure 1 This is a schematic diagram of the structure of an aluminum-plastic film according to an embodiment of this application. Figure 1 As shown, the aluminum-plastic film 10 includes a heat-sealing layer 11, a metal layer 12, and a functional material layer 13.

[0050] The electrode assembly is housed in the aluminum-plastic film 10, and the heat-sealing layer 11, the metal layer 12 and the functional material layer 13 are sequentially arranged in the direction away from the electrode assembly.

[0051] The functional material layer 13 includes functional materials, including urea groups.

[0052] The urea group consists of two nitrogen atoms linked by a carbon atom, and its structural formula is: The unique electron distribution of the urea group gives it characteristics such as strength, elasticity, and wear resistance in its spatial configuration. The functional material in the embodiments of this application includes urea groups, thus the functional material has good impact resistance, elasticity, and wear resistance.

[0053] Specifically, the nitrogen and oxygen atoms in the urea group have strong electronegativity, enabling them to form hydrogen bonds with other molecules or groups, enhancing intermolecular forces and giving the functional material high stability and mechanical strength. Simultaneously, the numerous hydrogen bonds increase both elasticity and intermolecular sliding stress, increasing frictional energy loss and improving the material's wear resistance. Secondly, molecules containing urea groups typically have a relatively regular structure, allowing for close packing within the material. This close packing increases van der Waals forces, further enhancing the stability of the urea group and the overall strength of the material. Furthermore, the carbonyl group in the urea group resonates with the lone pair electrons on the nitrogen atom, resulting in a more uniform electron cloud distribution and lower molecular energy, thus stabilizing the urea group and improving the stability of the functional material. Additionally, the C-N and C=O bonds in the urea group have relatively high bond energies, requiring significant energy to break, contributing to the urea group's stability and resistance to hydrolysis or other chemical reactions, thus ensuring the functional material's good stability. All of these factors contribute to the functional material's excellent impact resistance, elasticity, and abrasion resistance.

[0054] For example, the functional material may include a long, straight carbon chain, which can improve the extensibility and flexibility of the functional material. For example, the functional material may include at least one of polyurea materials and polyurethane materials containing urea groups.

[0055] Polyurea materials use urea groups as repeating units, and contain a large number of urea groups, which can greatly improve the extensibility, flexibility and elasticity of functional materials.

[0056] As an example, the metal layer 12 comprises aluminum. The metal layer 12 can prevent external water vapor from penetrating into the aluminum-plastic film 10.

[0057] As an example, the heat-sealing layer 11 includes a first sub-heat-sealing layer 111 and a second sub-heat-sealing layer 112. The first sub-heat-sealing layer 111 includes a heat-adhesive resin (e.g., polypropylene), antioxidants, slip agents, antistatic agents, acid-resistant agents, and solvent-resistant agents, etc. The second sub-heat-sealing layer 112 may include an acid-modified polyolefin, such as an ethylene-propylene copolymer modified with unsaturated carboxylic acids, which can enhance the adhesion between the heat-sealing layer and the metal layer 12.

[0058] As an example, a chemical conversion treatment layer 14 is provided between the metal layer 12 and the heat-sealing layer 11. The chemical conversion treatment layer 14 can be formed by reacting chromate with the surface of the aluminum metal layer 12 to improve the adhesion of the surface of the aluminum metal layer 12 and prevent corrosion of the aluminum metal layer 12.

[0059] In this embodiment, the outermost layer of the aluminum-plastic film 10, furthest from the electrode assembly, is the functional material layer 13. That is, the functional material layer 13 is located on the outermost side of the aluminum-plastic film 10 shell of the battery cell, and external impacts on the aluminum-plastic film 10 shell are primarily borne by the functional material layer 13. The functional material layer 13 contains urea groups, giving it excellent impact resistance, elasticity, and abrasion resistance. Therefore, when an external force impacts the functional material layer 13 (e.g., a dent in the aluminum-plastic film 10), the risk of damage or even breakage of the aluminum-plastic film 10 under external impact can be effectively reduced. Furthermore, during the use of the battery cell, the risk of friction-induced damage to the aluminum-plastic film 10 can be reduced, thereby improving the encapsulation reliability of the battery cell and reducing the risk of leakage.

[0060] In some embodiments, the functional material further includes a cyclic structure linked to a urea group, the cyclic structure comprising a carbon ring consisting of three or more carbon atoms linked together.

[0061] It should be noted that in the embodiments of this application, the urea group and the cyclic structure can be directly or indirectly connected. For example, the urea group and the cyclic structure can be connected by a carbon chain.

[0062] A cyclic structure consists of a carbon ring composed of three or more carbon atoms linked together. The bonds between two adjacent carbon atoms within the ring can be single, double, or triple bonds, and the number of rings can be one or more. For example, a cyclic structure can be a benzene ring.

[0063] In ring structures, atoms are arranged more tightly, with carbon atoms within the ring linked together by covalent bonds to form a closed ring system that is less prone to deformation and breakage. This geometry helps reduce bond strain and minimize energy loss due to changes in bond length. Therefore, ring structures exhibit higher rigidity, thereby improving the stability, strength, hardness, and modulus of functional materials.

[0064] In some embodiments, the impact strength K of the aluminum-plastic film 10 satisfies: 60 J / m 2 ≤K≤150J / m 2 .

[0065] For example, K can be 60 J / m 2 70J / m 2 75J / m 2 80J / m 290J / m 2 100J / m 2 110J / m 2 120J / m 2 130J / m 2 140J / m 2 150J / m 2 , or its value is within the range obtained by combining any two of the above values.

[0066] It should be noted that, in this embodiment of the application, the impact strength of the aluminum-plastic film 10 is the impact strength value obtained by performing an impact strength test on the aluminum-plastic film 10 from the side of the functional material layer 13.

[0067] In this embodiment, the impact strength of the aluminum-plastic film 10 is within the above-mentioned range, which has good impact resistance and can effectively reduce the risk of damage or even breakage of the aluminum-plastic film 10 under external impact, thereby improving the packaging reliability of the battery cell and reducing the risk of leakage of the battery cell.

[0068] In some embodiments, the thickness D of the functional material layer 13 satisfies: 5μm≤D≤30μm.

[0069] For example, D can be 5μm, 10μm, 12μm, 15μm, 20μm, 24μm, 25μm, 30μm, or a value within the range obtained by any combination of the above two values.

[0070] In this embodiment, the thickness of the functional material layer 13 is set within the above-mentioned range. On the one hand, this ensures that the thickness of the functional material layer 13 is sufficient to provide effective impact resistance. On the other hand, it avoids the functional material layer 13 being too thick and affecting the energy density of the battery cell. Therefore, the thickness setting of the functional material layer 13 in this application can both ensure that the aluminum-plastic film 10 has good impact resistance and improve the energy density of the battery cell.

[0071] In some embodiments, the bonding strength σ between the functional material layer 13 and the metal layer 12 satisfies: 40N / 10cm≤σ≤100N / 10cm.

[0072] For example, σ can be 40N / 10cm, 50N / 10cm, 60N / 10cm, 70N / 10cm, 80N / 10cm, 90N / 10cm, 100N / 10cm, or a value within the range obtained by any combination of the above two values.

[0073] In this embodiment, the bonding strength between the functional material layer 13 and the metal layer 12 is within the above-mentioned range, and the two have good adhesion. Therefore, there is no need to set an additional adhesive layer to bond the functional material layer 13 and the metal layer 12, which can simplify the preparation process, save production costs, and reduce the overall thickness of the aluminum-plastic film 10, which is beneficial to improving the energy density of the battery cell.

[0074] This application does not impose any particular limitation on the shape of the battery cell; it can be cylindrical, square, or any other arbitrary shape. The battery cell can be a lithium-ion battery, a lithium-sulfur battery, a sodium-ion battery, a magnesium-ion battery, etc.

[0075] Figure 2 This is a schematic diagram of a battery cell according to an embodiment of this application. For example, as shown... Figure 2 As shown, the battery cell 3 is a square battery cell. The battery cell 3 may include an outer packaging 31, which can be used to encapsulate the electrode assembly 32 and the electrolyte (not shown in the figure). Exemplarily, the outer packaging 31 can be a flexible packaging bag, such as an aluminum-plastic film 10.

[0076] The electrode assembly 32 can be made from a positive electrode, a negative electrode, and a separator through a winding process or a stacking process.

[0077] In some embodiments, the electrode assembly 32 includes an electrode assembly body 321 and a tab 322 extending from the electrode assembly body 321.

[0078] In some embodiments, individual battery cells can be assembled into a battery module. The number of individual battery cells contained in a battery module can be one or more, and the specific number can be selected by those skilled in the art based on the application and capacity of the battery module.

[0079] [Positive electrode plate]

[0080] The positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one surface of the positive current collector, the positive electrode film layer including a positive electrode active material.

[0081] As an example, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive current collector.

[0082] In some embodiments, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0083] In some embodiments, the positive electrode active material may be a known battery positive electrode active material. As an example, the positive electrode active material may include at least one of the following materials: lithium phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, this application is not limited to these materials, and other conventional materials that can be used as battery positive electrode active materials may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides include, but are not limited to, lithium cobalt oxides (such as LiCoO2), lithium nickel oxides (such as LiNiO2), lithium manganese oxides (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxides, lithium manganese cobalt oxides, lithium nickel manganese oxides, and lithium nickel cobalt manganese oxides (such as LiNi). 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also known as NCM) 333 LiNi 0.5 Co 0.2 Mn 0.3 O2 (also known as NCM) 523 LiNi 0.5 Co 0.25 Mn 0.25 O2 (also known as NCM) 211 LiNi 0.6 Co 0.2 Mn 0.2 O2 (also known as NCM) 622 LiNi 0.8 Co 0.1 Mn 0.1 O2 (also known as NCM) 811 )), lithium nickel cobalt aluminum oxide (such as LiNi) 0.85 Co 0.15 Al 0.05At least one of O2 and its modified compounds. Examples of lithium phosphates with an olivine structure include, but are not limited to, lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), lithium iron phosphate and carbon composites, lithium manganese phosphate (such as LiMnPO4), lithium manganese phosphate and carbon composites, lithium manganese iron phosphate, and lithium manganese iron phosphate and carbon composites.

[0084] In some embodiments, the positive electrode film layer may optionally include a binder. As an example, the binder may include at least one selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.

[0085] In some embodiments, the positive electrode film may optionally include a conductive agent. As an example, the conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0086] In some embodiments, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive active material, conductive agent, binder and any other components, in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry onto the positive electrode current collector, and then obtaining the positive electrode sheet after drying, cold pressing and other processes.

[0087] During the charging and discharging process of a battery, Li undergoes insertion / extraction and consumption, resulting in varying molar Li content at different discharge states. In the examples of cathode materials in this application, the molar Li content refers to the initial state of the material, i.e., the state before feeding. When the cathode material is applied to the battery system, the molar Li content changes after charge-discharge cycles.

[0088] In the examples of cathode materials in this application, the molar content of O is only a theoretical value. Oxygen release from the crystal lattice will cause changes in the molar content of oxygen, and the actual molar content of O will fluctuate.

[0089] [Negative electrode plate]

[0090] The negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector, the negative electrode film layer including a negative electrode active material.

[0091] As an example, the negative electrode current collector has two surfaces opposite each other in its own thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.

[0092] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0093] In some embodiments, the negative electrode film layer may optionally include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0094] In some embodiments, the negative electrode film may optionally include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0095] In some embodiments, the negative electrode film may optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na) or lithium carboxymethyl cellulose (CMC-Li)).

[0096] In some embodiments, the negative electrode sheet can be prepared by dispersing the components used to prepare the negative electrode sheet, such as the negative electrode active material, conductive agent, binder and any other components, in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto the negative electrode current collector, and then obtaining the negative electrode sheet after drying, cold pressing and other processes.

[0097] [Electrolytes]

[0098] The electrolyte acts as a conductor of ions between the positive and negative electrodes. This application does not impose specific limitations on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid, gel-like, or entirely solid.

[0099] In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent.

[0100] Electrolyte salts may include one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.

[0101] Solvents may include one or more of the following: ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.

[0102] The electrolyte may also optionally include negative electrode film-forming additives, positive electrode film-forming additives, and performance additives that can improve certain battery performance, such as performance additives that improve battery overcharge performance, battery high temperature or low temperature performance, etc.

[0103] [Isolation Component]

[0104] The separator is used to isolate the positive electrode and the negative electrode. This application does not impose any particular limitation on the type of separator; any known porous separator with good chemical and mechanical stability can be selected.

[0105] The material of the separator can be selected from one or more of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film; there are no particular restrictions. When the separator is a multi-layer composite film, the materials of each layer can be the same or different; there are no particular restrictions.

[0106] Positive electrode, negative electrode and separator can be made into electrode assembly by winding process or stacking process.

[0107] [Preparation methods for battery cells]

[0108] Figure 3 This is a schematic diagram of a method for preparing a battery cell according to an embodiment of this application. (In conjunction with...) Figure 3 As shown, the method 300 for preparing a single battery cell may include the following steps.

[0109] Step 310: Prepare aluminum-plastic film;

[0110] Step 320: The electrode assembly is housed in an aluminum-plastic film to prepare a battery cell.

[0111] The preparation of the aluminum-plastic film includes: providing a metal layer; preparing a heat-sealing layer on one side surface of the metal layer; and preparing a functional material layer on the other side surface of the metal layer. When the electrode assembly is housed within the aluminum-plastic film, the functional material layer is located away from the electrode assembly. The functional material layer includes a functional material, which includes urea groups.

[0112] In some embodiments, preparing a functional material layer on the other side surface of the metal layer includes: spraying a first component and a second component onto the other side surface of the metal layer, wherein the first component and the second component react on the other side surface of the metal layer to generate a functional material.

[0113] In some embodiments, the first component may include isocyanate monomers, polyols, pigments, and fillers.

[0114] For example, the isocyanate monomer may include at least one of toluene diisocyanate (TDI) and its isomers, and diphenylmethane diisocyanate (MDI) and its isomers; the polyol may include at least one of polyether polyol and polyester polyol; the pigment may include at least one of titanium dioxide and iron oxide; and the filler may include at least one of barium sulfate, silica powder, and calcium carbonate.

[0115] In some embodiments, the second component may include an amino-terminated resin, an amino-terminated chain extender, a leveling agent, and a defoamer.

[0116] For example, the amino-terminated resin may include at least one of amino-terminated polyether and amino-terminated polyester; the amino-terminated chain extender may include at least one of ethylenediamine, diethylenetriamine, and m-phenylenediamine; the leveling agent may include at least one of acrylate leveling agents, silicone leveling agents, fluorocarbon leveling agents, polyether-modified leveling agents, and composite leveling agents; and the defoamer may include at least one of silicone defoamers, polyether defoamers, fatty alcohol defoamers, and mineral oil defoamers.

[0117] The aforementioned isocyanate monomers can provide -NCO groups, and the amino-terminated resins can provide -NH2 groups. The isocyanate monomers and amino-terminated resins undergo a curing reaction to form functional materials containing urea groups. Simultaneously, adding polyol raw materials during the above chemical curing process can react with the isocyanate monomers to form prepolymers, adjusting the flexibility, hardness, and other properties of the functional materials. Adding pigments and fillers can further improve the mechanical strength, abrasion resistance, and other properties of the functional materials. Adding amino-terminated chain extenders can synergistically work with the amino-terminated resins to increase the length of the functional material's molecular chains, improving its strength, hardness, and other properties. Adding leveling agents and defoamers can improve the workability and quality of the functional material layers.

[0118] It should be noted that composite leveling agents refer to leveling agents formed by combining two or more leveling agents, such as acrylate leveling agents and silicone leveling agents.

[0119] In some embodiments, the volume ratio of the first component to the second component is 1:10 to 10:1.

[0120] For example, the volume ratio of the first component and the second component can be 1:10, 1:5, 1:2, 1:1, 2:1, 3:1, 5:1, 10:1, or a volume ratio within the range obtained by any combination of the above two volume ratios.

[0121] In some embodiments, the initial curing time t for the reaction of the first component and the second component on the other side surface of the metal layer satisfies: 1 min ≤ t ≤ 60 min.

[0122] For example, t can be 1 min, 5 min, 10 min, 15 min, 20 min, 25 min, 30 min, 40 min, 50 min, 60 min, or its value can be within the range obtained by any combination of the above two values.

[0123] In some embodiments, the initial curing temperature T of the reaction of the first component and the second component on the other side surface of the metal layer satisfies: 5℃≤T≤85℃.

[0124] For example, T can be 5℃, 10℃, 15℃, 20℃, 25℃, 30℃, 40℃, 50℃, 60℃, 70℃, 80℃, 85℃, or a value within the range obtained by any combination of the above two values.

[0125] It should be understood that in the embodiments of this application, the initial curing time and initial curing temperature of the first component and the second component refer to the time and reaction temperature during which the first component and the second component change from a gel state to a cured state after the first component and the second component begin to react.

[0126] It should be noted that during the reaction of the first and second components, reaction aids such as catalysts can be added to enable the first and second components to complete the curing reaction at a lower temperature and in a shorter time.

[0127] Setting the reaction conditions (volume ratio, initial curing time, and initial curing temperature) of the first and second components within the above range is beneficial for the two components to react fully, so as to generate a functional material with good impact resistance, elasticity, and wear resistance.

[0128] In some implementations, the preparation method 300 further includes perforating the aluminum-plastic film before accommodating the electrode assembly within it.

[0129] Punching refers to the process of punching a hole in an aluminum-plastic film to accommodate electrode components during the production of a battery cell, using a molding die under heating.

[0130] In the preparation method of this application embodiment, a functional material layer is prepared on the surface of the metal layer. The functional material layer contains urea groups, which can simultaneously improve the stability, strength, elasticity, and wear resistance of the functional material, giving it good impact resistance, elasticity, and friction resistance. Therefore, when the functional material layer is impacted by external force (e.g., dents in the aluminum-plastic film), the risk of damage or even breakage of the aluminum-plastic film under external impact can be effectively reduced. Furthermore, during the use of the battery cell, the risk of friction-induced damage to the aluminum-plastic film can be reduced, thereby improving the encapsulation reliability of the battery cell and reducing the risk of leakage.

[0131] [Battery]

[0132] This application provides a battery, including the battery cell described in the above embodiments. Figure 4 This is a schematic diagram of the structure of a battery according to an embodiment of this application. Figure 4 As shown, the battery 5 may include multiple battery cells 3 to meet different power usage requirements. The shape of the battery cell 3 in this embodiment can be set according to actual application. For example, the battery cell 3 can be as follows: Figure 2 The cuboid shown can also be different. Figure 2 The embodiments shown are cylindrical or other shapes, but are not limited to these.

[0133] It should be understood that, such as Figure 4 As shown, the battery 5 in this embodiment may further include a housing 51, which can be used to accommodate multiple battery cells 3. The housing 51 in this embodiment has a hollow interior, and the multiple battery cells 3 are accommodated within the housing 51. The housing 51 may include two parts, referred to herein as a first housing portion 511 and a second housing portion 512, which are fastened together. The shapes of the first housing portion 511 and the second housing portion 512 can be determined according to the shape of the components housed inside, for example, according to the shape of the combination of the multiple battery cells 3 housed inside. At least one of the first housing portion 511 and the second housing portion 512 has an opening. For example, as... Figure 4 As shown, the first housing portion 511 and the second housing portion 512 can both be hollow cuboids with one open side. The openings of the first housing portion 511 and the second housing portion 512 are opposite to each other, and the first housing portion 511 and the second housing portion 512 are interlocked to form a housing 51 with a closed cavity, which can be used to accommodate multiple battery cells 3. The multiple battery cells 3 are connected in parallel, series, or mixed and placed inside the housing 51 formed by the interlocking of the first housing portion 511 and the second housing portion 512.

[0134] For example, unlike Figure 4As shown, either the first housing portion 511 or the second housing portion 512 may have only one hollow cuboid with an opening, while the other is plate-shaped to cover the opening. Taking the second housing portion 512 as a hollow cuboid with one opening, and the first housing portion 511 as a plate-shaped example, then the first housing portion 511 covers the opening of the second housing portion 512 to form a housing 51 with a closed chamber, which can be used to accommodate multiple battery cells 3.

[0135] Battery cells 3 can be directly assembled into battery 5, or they can be first assembled into battery modules, and then multiple battery modules can be assembled into battery 5.

[0136] [Electrical appliances]

[0137] This application provides an electrical device, including the battery described in the above embodiments.

[0138] Figure 5 This is a schematic diagram of an electrical device according to an embodiment of this application. Figure 5 As shown, this application provides an electrical device 6, which includes the battery in the above embodiment.

[0139] Alternatively, the electrical device may also be an energy storage device, a lighting device, a spacecraft, etc., as is the case in the embodiments of this application.

[0140] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.

[0141] [Examples and Comparative Examples]

[0142] 1. Preparation of aluminum-plastic film

[0143] Aluminum-plastic film 1:

[0144] Preparation of the metal layer: The surface of the aluminum foil is treated to remove oil and oxides, and the surface of the aluminum foil is passivated with chromate. Finally, the aluminum foil is dried.

[0145] Preparation of the heat-sealing layer: Anhydride-modified polypropylene is coated onto one side of the metal layer by extrusion and cured at 40℃~50℃ for 48 hours to obtain the heat-sealing layer.

[0146] Preparation of functional material layers:

[0147] (1) Preparation of the first component: Weigh 55 parts by weight of diphenylmethane diisocyanate, 30 parts by weight of polyoxypropylene ether diol, 14 parts by weight of polyester diol, and 1 part by weight of titanium dioxide, and bake them in an oven at 50°C for 2 hours to remove moisture. Then, add the dehydrated polyoxypropylene ether diol, polyester diol, and titanium dioxide to the diphenylmethane diisocyanate in small batches. Stir and react for 4 hours under a nitrogen atmosphere at 60°C to obtain the first component.

[0148] (2) Preparation of the second component: At room temperature, 10 parts by weight of polyether triamine, 45 parts by weight of polyether diamine, 10 parts by weight of 4,4'-bis(sec-butylamino)-diphenylmethane, 34.5 parts by weight of diethyltoluene diamine, and 0.5 parts by weight of polydimethylsiloxane were weighed and added to a mixing tank and stirred until homogeneous to obtain the second component.

[0149] The first and second components were placed in a spraying equipment at a mass ratio of 1:1. After being heated (25℃-40℃) and pressurized (15MPa-25MPa) and accurately metered, they were mixed in a dynamic mixing chamber and then sprayed evenly onto the other side of the metal layer. Under the reaction conditions of an initial curing temperature T of 50℃ and an initial curing time t of 30min, a gel was formed and initially cured. After being placed in an environment of 23℃±2℃ and 50±5% humidity for 7 days, a functional material layer was formed, resulting in aluminum-plastic film 1.

[0150] Aluminum-plastic film 2-3: The preparation of aluminum-plastic film 2-3 is similar to that of aluminum-plastic film 1, except that the t values ​​in the preparation process of aluminum-plastic film 2-3 are 1 min and 60 min, respectively.

[0151] Aluminum-plastic film 4-5: The preparation of aluminum-plastic film 4-5 is similar to that of aluminum-plastic film 1, except that the temperature T is 5℃ and 85℃ respectively during the preparation of aluminum-plastic film 4-5.

[0152] Aluminum-plastic film 6: The preparation of aluminum-plastic film 6 is similar to that of aluminum-plastic film 1. The difference is that the pit depth is 8μm during the preparation of aluminum-plastic film 6.

[0153] Aluminum-plastic film 7: In the preparation process of aluminum-plastic film 7, the preparation of heat-sealing layer and metal layer is the same as that of aluminum-plastic film 1. The difference is that aluminum-plastic film 7 does not include functional material layer. Instead, a substrate layer is prepared on the other side of metal layer. Specifically, adhesive is applied to both sides of polyamide resin. One side of the adhesive is bonded to the metal layer, and the other side of the adhesive is bonded to polyamide resin. After drying, curing and hot pressing composite treatment, the substrate layer is formed. The thickness D' of the substrate layer is 33μm.

[0154] Aluminum-plastic film 8: The preparation of aluminum-plastic film 8 is similar to that of aluminum-plastic film 7. The difference is that the thickness D' of the substrate layer is 25μm during the preparation of aluminum-plastic film 8.

[0155] Aluminum-plastic film 9: The preparation of aluminum-plastic film 9 is similar to that of aluminum-plastic film 7. The difference is that the pit depth is 8μm during the preparation of aluminum-plastic film 9.

[0156] [Example 1]

[0157] (1) Aluminum-plastic film

[0158] The aluminum-plastic film used is the aluminum-plastic film 1 prepared as described above.

[0159] (2) Preparation of positive electrode sheet

[0160] Lithium iron phosphate (LiFePO4), conductive carbon black, and PVDF (PVDF) were mixed in a mass ratio of 8:1:1 and dissolved in N-methylpyrrolidone (NMP). The mixture was thoroughly stirred and homogenized to prepare a positive electrode slurry. This slurry was then uniformly coated onto two opposite surfaces of an aluminum foil current collector. After drying, cold pressing, and slitting, the positive electrode sheet was rolled into a film roll. A ceramic slurry was then sprayed onto the slit surfaces of the film roll. In the ceramic slurry, boehmite was the ceramic material, comprising 39% by weight; polyacrylate was the binder, comprising 5% by weight; N-methylpyrrolidone was the solvent; the solid content of the ceramic slurry was 10%; and the viscosity of the ceramic slurry was 800 mPa·s.

[0161] (3) Preparation of negative electrode sheet

[0162] Artificial graphite (anode active material), conductive carbon black (conductive agent), carboxymethyl cellulose (CMC) (binder), and water (solvent) are mixed in a weight ratio of 95:2:3:100 and thoroughly stirred to prepare a negative electrode slurry. The negative electrode slurry is then uniformly coated on two opposite surfaces of a copper foil current collector. After drying, cold pressing, and slitting, the negative electrode sheet is obtained.

[0163] (4) Separation membrane: Conventional polyethylene membrane is used.

[0164] (5) Preparation of electrolyte: Ethyl carbonate (EC), diethyl carbonate (DEC) and dimethyl carbonate (DMC) are mixed in a volume ratio of 1:1:1, and then LiPF6 is uniformly dissolved in the above solution to obtain an electrolyte with a concentration of 1 mol / L.

[0165] (6) Preparation of lithium-ion battery: The above positive electrode sheet, separator and negative electrode sheet are stacked and wound in sequence to obtain electrode assembly; the electrode assembly is placed in aluminum-plastic film 1, the electrolyte prepared above is added, and after encapsulation, standing, formation and aging processes, a battery cell is obtained.

[0166] The battery cells of Examples 2-6 and Comparative Examples 1-3 were prepared using methods similar to those of the battery cell of Example 1, the difference being the use of different aluminum-plastic films (Aluminum-plastic film 1-6 was used in Examples 1-6, and aluminum-plastic film 7-9 was used in Comparative Examples 1-3), as detailed in Table 1. Performance parameters of Examples 1-6 and Comparative Examples 1-3 are shown in Table 1.

[0167] Table 1. Product parameters and performance parameters of Examples 1-6 and Comparative Examples 1-3

[0168]

[0169] In Table 1, t represents the initial curing time of the reaction of the first and second components on the surface of the metal layer; T represents the initial curing temperature of the reaction of the first and second components on the surface of the metal layer; D represents the thickness of the functional material layer; D' represents the thickness of the substrate layer; K represents the impact strength of the aluminum-plastic film; σ represents the bonding strength between the functional material layer and the metal layer; σ' represents the bonding strength between the substrate layer and the metal layer; whether or not leakage occurs refers to whether the lithium-ion battery leaks after 800 cycles.

[0170] The following is a brief description of the testing methods for the physicochemical and performance parameters involved in the embodiments of this application. It should be understood that the following testing methods are only examples, and other testing methods known in the art can also be used for testing.

[0171] 1. Impact strength test

[0172] In this embodiment, the impact strength test of the aluminum-plastic film is performed according to the national standard GB / T8017-2008. The kinetic energy calculation formula is kinetic energy E. 动 = m * g * h, where m is the mass of the falling hammer, g is the acceleration due to gravity, and h is the impact height. The formula for calculating impact strength K is K = E. 动 / S, where S is the impact contact area.

[0173] 2. Bond strength test

[0174] The bond strength between the functional material layer and the metal layer in this application can be determined by a peel test. The specific steps are as follows:

[0175] The prepared aluminum-plastic film sample is fixed on a platform, and then the functional material layer is slowly peeled off the metal layer at a specific angle (e.g., 90 degrees or 45 degrees). The force or energy required during the separation process is measured (and averaged). The reference standard can be ASTM D903 (peel strength of aluminum-plastic composite films) or ISO 11242.

[0176] 3. Aluminum-plastic film radius (R-angle) thickness test

[0177] The radius (R) thickness of aluminum-plastic film can be tested using the iEDX-150AT aluminum-plastic film radius thickness tester. The specific steps are as follows:

[0178] a. First, calibrate the equipment using standard sheets (such as 20μm, 30μm, and 40μm standard sheets) to ensure measurement accuracy.

[0179] b. The aluminum-plastic film sample to be tested is placed in the R-angle test fixture to ensure that the sample surface is flat and free of contamination.

[0180] c. Place the fixture containing the sample on the sample stage, ensuring accurate sample positioning for subsequent measurements.

[0181] d. Turn on the power of the tester and start the accompanying MultiRay analysis software.

[0182] e. Use a high-definition camera to monitor the sample position and select the measurement point in the R-angle area using the mouse.

[0183] f. After the instrument focuses on the measurement point, click the "Start Measurement" button. The instrument will perform X-ray scanning and data acquisition. Depending on the sample, the measurement time is generally 5 to 30 seconds. After the measurement is completed, the software will display the measurement results.

[0184] 4. Is there any leakage?

[0185] At room temperature (25℃), the lithium-ion battery is charged at a rate of 0.33C to a voltage of 4.2V, and then discharged at a rate of 0.33C to a voltage of 2.5V. The reversible capacity is measured as C0. The above steps are repeated until the lithium-ion battery has undergone 800 cycles, and then the lithium-ion battery is observed to see if leakage occurs.

[0186] 5. Confirmation of urea group and cyclic structure

[0187] Urea groups and cyclic structures can be detected using infrared spectroscopy. Specifically, urea groups typically appear as 1330 in the infrared spectrum. -1 ~1360cm -1 The characteristic absorption peaks of the ring structure are at 1600; -1 ~1800cm -1 It exhibits characteristic absorption peaks.

[0188] Based on the results of Examples 1-5 and Comparative Examples 1-2, it can be seen that by setting a urea-based functional material on the outer side of the aluminum-plastic film to form a functional material layer, the impact resistance of the aluminum-plastic film is significantly improved. Even without an adhesive, the functional material layer and the metal layer have good bonding strength. Furthermore, under the same dent depth, the aluminum-plastic film with the functional material layer has a thicker R-angle thickness, and the lithium-ion battery does not leak.

[0189] Based on the results of Example 6 and Comparative Example 3, it can be seen that by setting a urea-based functional material on the outside of the aluminum-plastic film to form a functional material layer, the impact resistance of the aluminum-plastic film is significantly improved. Even without an adhesive, the functional material layer and the metal layer have good bonding strength. Furthermore, under the same dent depth, the aluminum-plastic film with the functional material layer has a thicker R-angle thickness, and the lithium-ion battery does not leak.

[0190] Based on the results of Examples 1-6 and Comparative Examples 1 and 3, it can be seen that when a functional material layer is provided on the outside of the aluminum-plastic film, there is no need to provide an additional adhesive layer between the functional material layer and the metal layer. The functional material layer and the metal layer still have good adhesive strength, and the overall thickness of the aluminum-plastic film is reduced, which is beneficial to improving the energy density of the battery cell.

[0191] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A battery cell, characterized in that, include: Electrode assembly; An aluminum-plastic film is used to accommodate the electrode assembly. The aluminum-plastic film includes a heat-sealing layer, a metal layer, and a functional material layer, which are sequentially arranged along a direction away from the electrode assembly. The functional material layer includes functional materials, and the functional materials include urea groups.

2. The battery cell according to claim 1, characterized in that, The functional material also includes a cyclic structure connected to the urea group, wherein the cyclic structure comprises a carbon ring composed of three or more carbon atoms.

3. The battery cell according to claim 1 or 2, characterized in that, The functional material includes at least one of polyurea material and polyurethane material containing urea groups.

4. The battery cell according to any one of claims 1 to 3, characterized in that, The impact strength K of the aluminum-plastic film satisfies: 60 J / m 2 ≤K≤150J / m 2 .

5. The battery cell according to any one of claims 1 to 4, characterized in that, The thickness D of the functional material layer satisfies: 5μm≤D≤30μm.

6. The battery cell according to any one of claims 1 to 5, characterized in that, The bonding strength σ between the functional material layer and the metal layer satisfies: 40N / 10cm≤σ≤100N / 10cm.

7. A method for preparing a single battery cell, characterized in that, include: Preparation of aluminum-plastic film; The electrode assembly is housed in the aluminum-plastic film to prepare the battery cell; The preparation of the aluminum-plastic film includes: Provide a metal layer; A heat-sealing layer is prepared on one side surface of the metal layer; A functional material layer is prepared on the other side surface of the metal layer; In the case where the electrode assembly is housed within the aluminum-plastic film, the functional material layer is located away from the electrode assembly, and the functional material layer comprises functional materials, including urea groups.

8. The preparation method according to claim 7, characterized in that, The step of preparing a functional material layer on the other side surface of the metal layer includes: The first component and the second component are sprayed onto the other side surface of the metal layer, and the first component and the second component react on the other side surface of the metal layer to generate the functional material.

9. The preparation method according to claim 8, characterized in that, The first component includes isocyanate monomers, polyols, pigments, and fillers.

10. The preparation method according to claim 9, characterized in that, The isocyanate monomer includes at least one of toluene diisocyanate and its isomers, and diphenylmethane diisocyanate and its isomers; The polyol includes at least one of polyether polyol and polyester polyol; The pigment includes at least one of titanium dioxide and iron oxide; The filler includes at least one of barium sulfate, silica powder, and calcium carbonate.

11. The preparation method according to any one of claims 8 to 10, characterized in that, The second component includes an amino-terminated resin, an amino-terminated chain extender, a leveling agent, and a defoamer.

12. The preparation method according to claim 11, characterized in that, The amino-terminated resin includes at least one of amino-terminated polyether and amino-terminated polyester. The terminal amino chain extender includes at least one of ethylenediamine, diethylenetriamine, and m-phenylenediamine; The leveling agent includes at least one of acrylate leveling agents, silicone leveling agents, fluorocarbon leveling agents, polyether modified leveling agents, and composite leveling agents; The defoamer includes at least one of the following: silicone defoamer, polyether defoamer, fatty alcohol defoamer (octanol, decanol), and mineral oil defoamer.

13. The preparation method according to any one of claims 8 to 12, characterized in that, The volume ratio of the first component to the second component is 1:10 to 10:

1.

14. The preparation method according to any one of claims 8 to 13, characterized in that, The initial curing time t for the reaction of the first component and the second component on the other side surface of the metal layer satisfies: 1min ≤ t ≤ 60min.

15. The preparation method according to any one of claims 8 to 14, characterized in that, The initial curing temperature T of the reaction of the first component and the second component on the other side surface of the metal layer satisfies: 5℃≤T≤85℃.

16. An electrical appliance, characterized in that, Includes battery cells according to any one of claims 1 to 6, and / or battery cells prepared by the method according to any one of claims 7 to 15.